The Biological Potential of Silver Nanoparticles Made from the Sargassum tenerrimum seaweed extract. - V. Parthiban; K. Kalarani (The Bioscan, 2025)
Silver nanoparticles (AgNPs) have been extensively studied for their potential biological applications due to their unique physical and chemical properties. The Sargassum tenerrimum seaweed extract has been found to be a potential source for the synthesis of AgNPs. In this study, we have investigated the biological potential of AgNPs synthesized from Sargassum tenerrimum extract. Through dispersive X-ray analysis, Fourier Transformer Infrared Spectroscopy analysis, among other methods of research, these AgNPs have been shown to have strong antimicrobial activity against a variety of microorganisms, including bacteria, fungi, and viruses. Additionally, they have been shown to have antioxidant, anti-inflammatory, and wound-healing properties. Research and observations thus showed the antibacterial activity of green synthesized AgNPs using Solanum torvum leaf extract. Observations have also indicated the presence of anti-cancer properties of silver nanoparticles.